Yield to the resistance: The impact of nematode resistant varieties on alfalfa yield. (1st November 2017) - Jordan, Scott
Abstract : Abstract: Alfalfa is a major cash crop in the western United States, where fields that are infested with the alfalfa stem nematode ( Ditylenchus dipsaci ) can be found. With no nematicides available to control alfalfa stem nematode spread, growers can use nematode resistant varieties of alfalfa to manage nematode populations in a field. A deterministic, discrete‐time, host‐parasite model is presented that describes the spread of alfalfa stem nematodes on resistant hosts that were fit to experimental data obtained in Weber County, Utah. Numerical results obtained from simulations with the model are used to compare how varying levels of resistance can affect harvest yield. Recommendations for Resource Managers: Alfalfa stem nematodes have a significant impact on alfalfa production. Nematode resistant varieties of alfalfa can be used to lessen the impact of nematodes on the alfalfa. This discrete deterministic model is used to determine how different levels of nematode resistance in these varieties will affect harvest yield and nematode populations in the field. Alfalfa varieties that have a resistance to nematodes can improve yield and lower the nematode population in an infested field.